Commotio cordis: A review. (July 2017) - Menezes, Ritesh G; Fatima, Huda; Hussain, Syed Ather; Ahmed, Saba; Singh, Pankaj Kumar; Kharoshah, Magdy A; Madadin, Mohammed; Ram, Pradhum; Pant, Sadip; Luis, Sushil Allen
Commotio cordis is an increasingly reported fatal mechano-electric syndrome and is the second most common cause of sudden cardiac death in young athletes. It is most commonly associated with a sports-related injury, wherein, there is a high-velocity impact between a projectile and the precordium. By virtue of this impact, malignant arrhythmias consequently develop leading to the individual's immediate demise, accompanied by a relatively normal post-mortem analysis. The importance of an autopsy remains paramount to exclude other causes of sudden death. With increasing awareness and reporting, survival rates are beginning to improve; however, prevention of the development of this condition remains the best approach for survival.